As territorialidades institucionais e dos empreendimentos econômicos turísticos na APA e Resex Marinha Delta do Parnaíba - Carvalho, Rita de Cássia Pereira de (2018)
The geographical approach in protected natural areas contributes to the understanding of their relations in a territorial perspective and of development. This research refers to the institutional territorialities and tourist economic enterprises (tourism agencies) of the Environmental Protection Area (APA) and Extractive Reserve (RESEX) Marinha Delta do Parnaíba, MA, PI and CE, which are two Conservation Units (UC's) superimposed on the same territory. They cover ten municipalities: Araioses, Água Doce do Maranhão, Tutoia and Paulino Neves, in the state of Maranhão, Ilha Grande, Parnaíba, Luís Correia and Cajueiro da Praia, in the state of Piauí, Barroquinha and Chaval, in the state of Ceará, and this UC’s integrate the tourist route, Route of Emotions. The choice of this territory is made by its singularities and diversities that seek to balance the use and occupation. Its objective is to analyze how the institutional territorialities and economic tourism enterprises of these, and how they contributed to the territorial development, from the understanding of the geographical concepts of territory and territorialities and their geoenvironmental and socioeconomic characterization. The method adopted is the inductive one. With regard to the problem, the mixed method is used to reconcile the quantitative and qualitative approach. The subjects involved in the research are the managing bodies of the UC's, 10 tourism agencies, which were chosen with the criterion of the active register in the platform of CADASTUR (System of registration of individuals and legal entities that operate in the tourism sector) and visitors, which were delimited from the infinite sample (625), since there are no preliminary studies that quantify the visitation. The data (questionnaires) are described and the guided interviews are analyzed based on the method of content analysis proposed by Bardin (2011). We realize that there is the difficulty in controlling the entrance to the visitation, given the extension of the territory. The main activity of the APA and RESEX Marinha Delta of Parnaíba is tourism, and in specific the segment of ecotourism, although mischaracterized. It is still an activity that needs planning and planning, so that it can assume an inclusive and participative character, by increasing the traditional knowledge and activities of the communities. However, the management bodies and sought to articulate with these groups that influence and are influenced in this area, the participatory construction of the management plan and that this document contemplates the use and occupation in the perspective of territorial development, besides the ordering of the uses of these UC’s.